Comparison of maternal serum and neonatal cord blood levels of zinc in relation to birth weight and period of gestation - Ahmed, Shabbeer; Sagar, Avula Kanthi (International Journal of Contemporary Pediatrics, 2021)
Background: Women are at increased risk of zinc deficiency during pregnancy because of high fetal requirements for zinc. Severe maternal zinc deficiency has been associated with poor fetal growth, spontaneous abortion and congenital malformations (i.e., anencephaly), whereas milder forms of zinc deficiency have been associated with low birth weight (LBW), intrauterine growth retardation, and preterm delivery. However, the research relating maternal zinc status and birth weight has not produced consistent results. This study has been undertaken to confirm the association between maternal serum zinc concentration and birth weight and period of gestation in setting like India. Methods: A total of 100 new-borns were included and divided into two groups, the ‘study group’ had babies with birth weight <2.5 kg and control group’ with babies >2.5 kg birth weight. Cord blood from the new-borns and serum samples of mothers were collected and the zinc levels were measured. Results: The correlation of cord blood and the maternal serum zinc levels were assessed in relation to birth weight and the gestational age. The results were compared between the two groups. The difference in values between the two groups was statistically significant, maternal serum zinc levels and birth weight (84.78±21.62 vs 66.04±18.66) (‘P’ value 0.04), cord blood zinc levels and birth weight (98.44±22.59 vs 79.78±19.54) (‘P’ value <0.001). The maternal serum and cord blood zinc was compared between the preterm and term; the results were statistically significant. Conclusions: The maternal and cord blood levels of zinc are correlated well with the birth weight and the gestational age at delivery. Supplementation of zinc during gestation might help reduce the incidence of IUGR and the risk of prematurity.